Critical Drug Shortages: Implications for Emergency Medicine. (June 2014) - Mazer‐Amirshahi, Maryann; Pourmand, Ali; Singer, Steven; Pines, Jesse M.; van den Anker, John; Schneider, Sandra
Abstract Prescription drug shortages have become increasingly common and more severe over the past decade. In addition, reported shortages are longer in duration and have had a greater effect on patient care. Some of the causes of current drug shortages are multifactorial, including the consolidation of drug manufacturers, quality problems at production plants that restrict the supply of drugs, and a lack of financial incentives for manufacturers to produce certain products, particularly generic medications. Generic injectable medications are most commonly affected by shortages because the production process is complex and costly for these drugs, and profit margins are often smaller than for branded medications. Many commonly used emergency department (ED) generic injectables have been affected by shortages, including multiple resuscitation and critical care drugs. Several reports have shown that shortages can potentially have major effects on the quality of medical care, including medication errors, treatment delays, adverse outcomes, and increased health care costs. Currently, no published data exist outside of case reports that directly link ED‐based drug shortages to overall patient safety events; however, there are several examples in the ED where first‐line therapies for life‐saving medications have been in short supply, and alternatives have higher rates of adverse events, narrower therapeutic indexes, or both. Aside from increasing notification about shortages, the U.S. Food and Drug Administration has little power to coerce manufacturers to produce medications during a shortage. Therefore, ED providers must learn to mitigate the effects of shortages locally, through active communication with pharmacy staff to identify safe and effective alternatives for commonly used medications when possible. Particularly given the effect on critical care medications, therapeutic alternatives should be clearly communicated to all staff so that providers have easy access to this information during resuscitations. This review focuses on the etiology of drug shortages, their effect on the ED, and potential solutions and mitigation strategies.